Three-Dimensional Analysis of Maxillary Expansion during Mixed Dentition: Comparison between Leaf Expander and Aligners—A Case-Control Study - Francesca Silvestrini-Biavati; Sirus Imenpour; Francesca Poli; Elis Kola; Andrea Abate; Valentina Lanteri; Alessandro Ugolini (Applied Sciences)
The objective of this retrospective study was to compare the dento-alveolar effects of two different expansion protocols, Invisalign First (IF) and Leaf Expander (LE), in patients in mixed dentition with transversal upper maxillary deficiency. Materials and Methods: 30 patients were treated with IF, whereas 38 patients were treated with LE. For each sample 3D digital cast models were analyzed pre and post expansion and transversal diameter of the upper arch, molar rotation and inclination and arch perimeter were measured. Results: LE resulted in a more significant expansion of the molar width and the arch perimeter, with less effect on the expansion of deciduous canines and deciduous molars. IF allowed a more effective molar derotation, but with a greater buccal tipping movement than LE, which determines a more bodily movement of the molars: the expansion determined by IF seems to be more dental than skeletal. Conclusions: IF is a good alternative to LE in case of limited transversal maxillary contraction, particularly when there is a significant mesio-rotation of the first upper molars.